An Alternative System for Eccentrically Braced Frames Resisting Lateral Loads - Bishay-Girges, N. W. (Engineering, Technology & Applied Science Research, 2019)
Eccentrically braced steel frames are structures used to resist lateral loads as they combine the ductility that is characteristic of moment frames and the stiffness associated with braced frames. Damper devices can be used as the main source of energy dissipation and have become more popular lately for the lateral control of structures. Control devices generally reduce damage by increasing structural safety, serviceability and preventing the building from collapse during vibration. This study focused on improving the performance of the structures with a proposed damping system, which has more advantages than eccentrically braced frames (EBFs). It can accommodate many architectural features and make construction and complementarity in the structures easier. The purpose of this study is to evaluate the performance of the structure with the proposed damping system and its construction in the building.